3D printing of hydrogels for biofabrication - Woo, Priscilla Wei Hui (2016)
3D biofabrication allowed the construction of bio materials, tissues, cells, drugs and others to take on different shapes and forms, providing greater prospect for health solutions, opportunities for the handicap, development of readily available medical products, research advancement and many more. Properties of an ideal printable bio ink should exhibit sustainable biomaterial characteristics, good physical and chemical bond, the ability to deform under shear and maintain a desired structure after printing. Hydrogels prepared in this study are scrutinized based on its ability to deliver structurally stable scaffolds for biofabrication, neglecting the biomaterial component. Six combinations of hydrogels were prepared through the crosslinking of two out of the four polymers used, namely, alginate, gelatin, chitosan and kappa carrageenan. Each hydrogel was prepared and maintained under the same environmental conditions. The rheological properties were examined, selecting few samples that were deemed to fall within printable range. Results showed that a consistent and well mixed material is the first step to achieving a printable material, presence of residues or inhomogeneity will prevent ink extrusion. Followed by the gelation strength, a liquid like hydrogel state would define a weak printed structure, vice versa. However, a solid hydrogel presenting a brittle-like structure will affect the printing resolution and accuracy as observed in gelatin-kappa carrageenan hydrogel. Hence, the optimal gelation strength varies for each individual material. Deformation under shear is another critical characteristic that an ink should possess. It was found to be co-related to the permissibility of extrusion. Therefore, this study can help to redefine the prerequisite required of a material for 3D bioprinting.